2010
DOI: 10.4028/www.scientific.net/kem.426-427.537
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Optimization of Shot Peening Parameters on Surface Integrity of NAK80

Abstract: Shot peening is known to improve the fatigue performance of materials. The improvement in fatigue is that plastic deformation in the surface increases hardness, yield stress and microstrain of thinning Crystal block and dislocation density, and formed advantaged compress residual stress that are introduced into the near-surface of the components and which hinder crack initiation and growth. But over peening effect is produced when shot peening strengthening goes beyond a certain limit, which was adverse to imp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 7 publications
0
9
0
Order By: Relevance
“…Miao et al found that the surface quality and fatigue life of NAK80 steel could be improved by the shot peening. 1) However, the shot peening would cause deformation or cracking of the work pieces easily, which can't meet the surface quality requirements of precise mold. Therefore, some other advanced surface treatment technologies should be used in order to reduce the deformation of mold during surface treatment.…”
Section: Introductionmentioning
confidence: 99%
“…Miao et al found that the surface quality and fatigue life of NAK80 steel could be improved by the shot peening. 1) However, the shot peening would cause deformation or cracking of the work pieces easily, which can't meet the surface quality requirements of precise mold. Therefore, some other advanced surface treatment technologies should be used in order to reduce the deformation of mold during surface treatment.…”
Section: Introductionmentioning
confidence: 99%
“…Notably, material hardening is a favourable product of SP which directly enhances the hardness of the target material 4,72,109 by increasing the yield stress of the material. 5,110 Material hardening occurs due to the dislocations within the crystals of the material. 5,111 The comprehensive process of the formation of these dislocations is nicely detailed by Kirk 111 where it was reported that material hardening was affected by several parameters of SP, such as intensity 5 and peening time.…”
Section: Numerical Evaluation Of Residual Stress and Strain Hardeningmentioning
confidence: 99%
“…Petit-Renaud et al 115 established an empirical relationship between input variables, such as exposure time and nozzle size, and response variables (residual stresses and their corresponding distance to the target surface); and based on this relationship, they optimised the process parameters. Miao et al 5 independently considered the surface integrity as the optimisation objective to optimise a SP process. Later, using genetic algorithm, Baskaran et al 11 set the increase in residual compressive stress, reduction in surface roughness and cold work as objectives of an optimisation function and achieved an optimised set of parameters.…”
Section: Optimisation Algorithmsmentioning
confidence: 99%
See 1 more Smart Citation
“…Petit-Renaud, et al [13] established an empirical relationship between parameters of a typical shot peening process and measures of residual stress, and based on this relationship they optimized the parameters with a single objective optimisation function. Miao, et al [14] explored the relationship between parameters and residual stresses and surface roughness, and independently considered the surface integrity as the optimisation objective to optimise a shot peening process. Later, using the design and analysis of computer experiments method, Maximisation of residual compressive stress, minimisation of surface roughness and cold work were set as objectives of optimisation function by Bhuvaraghan, et al [15].…”
Section: Introductionmentioning
confidence: 99%